2010
DOI: 10.1136/adc.2010.192518
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary evaluation of a new technique of minimally invasive surfactant therapy

Abstract: Surfactant can be effectively delivered via a vascular catheter, and this method of MIST deserves further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
162
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(167 citation statements)
references
References 35 publications
(36 reference statements)
4
162
1
Order By: Relevance
“…As a result, the minimally invasive surfactant administration (MIST) technique has been proposed as an alternative, in which, following direct laryngoscopy, the surfactant is slowly administered through a thin tracheal catheter to infants capable of spontaneous breathing and supported by CPAP. This technique does not require the administration of sedatives or the use of positive pressure ventilation and causes less damage to the airways and is well-tolerated by tinier infants (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the minimally invasive surfactant administration (MIST) technique has been proposed as an alternative, in which, following direct laryngoscopy, the surfactant is slowly administered through a thin tracheal catheter to infants capable of spontaneous breathing and supported by CPAP. This technique does not require the administration of sedatives or the use of positive pressure ventilation and causes less damage to the airways and is well-tolerated by tinier infants (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…17 Alternatively, a semirigid vascular catheter can be guided through the vocal cords without a trochar or forceps. 18 Laryngeal mask airways have been used for surfactant administration in a study of premature infants between 880 and 2520 g, 76 and a recent RCT has confirmed that this technique achieves effective surfactant delivery. 77 Aerosolized surfactant would be the least invasive and probably most desirable way of administering surfactant.…”
mentioning
confidence: 99%
“…13,37 In this regard, nCPAP with surfactant treatment during spontaneous breathing is a promising option because it allows to combine avoidance of eMV with early surfactant administration. [17][18][19]36 It is worth noting that 33% to 83% of study patients in the noninvasive treatment groups needed eMV at some point during their clinical course (Table 1). It is possible that these patients still benefited with regard to BPD reduction because eMV was avoided during the postnatal transition period when their lungs were particularly vulnerable.…”
mentioning
confidence: 99%
“…This has led to a search for alternative strategies of providing exogenous surfactant using noninvasive or minimally invasive techniques which essentially avoid the use of an endotracheal tube; collectively labelled as 'minimally invasive surfactant therapy' (MIST) [Gupta and Donn, 2012]. These include pharyngeal instillation of surfactants [Kattwinkel et al 2004], administration via laryngeal mask airway [Trevisanuto et al 2005] and administration via a thin endotracheal catheter/feeding tube [Dargaville et al 2011]. The protocols for using these techniques are described in the individual publications but these are observational studies and their safety and efficacy is still not validated in controlled trials, and hence not generalizable to other units.…”
Section: Exogenous Surfactant Replacement Therapymentioning
confidence: 99%